Analysis of Madrasah Choice Determinants through the Integration of the EKB Model and SERVQUAL - Anshori Ahmad; Suwandi Suwandi (JIEM (Journal of Islamic Education Management), 2026)
This study aims to analyze the determinants of madrasah selection by integrating the Engel, Kollat, and Blackwell consumer behavior model and the SERVQUAL service quality framework at MAN 3 Kediri. The background of this study is the increasingly competitive environment among secondary educational institutions, which requires madrasahs to understand the factors influencing students’ school choice decisions. This research employed a quantitative associative-causal approach. The population consisted of 1,308 students of MAN 3 Kediri, with 297 respondents selected using proportionate stratified random sampling. Data were collected through a closed-ended questionnaire that had passed validity and reliability testing, and were analyzed using multiple linear regression with IBM SPSS version 27. The findings show that consumer behavior has a positive and significant effect on school choice and serves as the dominant factor with an effective contribution of 28.0%. Service quality also has a positive and significant effect, with an effective contribution of 13.7%. Simultaneously, both variables contribute 56.3% to school choice decisions. These findings indicate that madrasah selection is shaped by consumer preferences and perceived service quality.Keywords : consumer behavior, SERVQUAL, madrasah choice, EKB model, service quality